BS EN ISO 16486-4. Plastics piping systems for the supply of gaseous fuels. Unplasticized polyamide (PA-U) piping systems with fusion jointing and mechanical jointing. Part 4. Valves (1st April 2021) - British Standards Institution,
No abstract available